2022
DOI: 10.3847/1538-4365/ac6b3b
|View full text |Cite
|
Sign up to set email alerts
|

A Publicly Available Multiobservatory Data Set of an Enhanced Network Patch from the Photosphere to the Corona

Abstract: New instruments sensitive to chromospheric radiation at X-ray, UV, visible, IR, and submillimeter wavelengths have become available that significantly enhance our ability to understand the bidirectional flow of energy through the chromosphere. We describe the calibration, coalignment, initial results, and public release of a new data set combining a large number of these instruments to obtain multiwavelength photospheric, chromospheric, and coronal observations capable of improving our understanding of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…A linear fit to the trend gave a slope of 6.12 × 10 −5 Å/K. Kobelski et al (2022) confirmed this strong correlation between the two quantities for a region of weakly enhanced network magnetic field in the quiet Sun. They reported a steeper slope of 1.1 × 10 −4 Å/K over a narrower range of observed temperatures, due to their more quiet target region.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…A linear fit to the trend gave a slope of 6.12 × 10 −5 Å/K. Kobelski et al (2022) confirmed this strong correlation between the two quantities for a region of weakly enhanced network magnetic field in the quiet Sun. They reported a steeper slope of 1.1 × 10 −4 Å/K over a narrower range of observed temperatures, due to their more quiet target region.…”
Section: Introductionsupporting
confidence: 66%
“…The present work uses two data series taken from the more extensive coordinated data set described in Kobelski et al (2022) 1 . The full data set includes coordinated observations between ALMA and multiple instruments at each of the Dunn Solar Telescope (DST), IRIS, Hinode spacecraft, and SDO facilites; the Nuclear Spectroscopic Telescope Array (NuSTAR) also observed the same solar target within several hours of our observations.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations